2021
DOI: 10.1111/jvs.13072
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging and soil but not seedling competition structure tree communities in a catchment containing a tropical freshwater swamp forest

Abstract: Questions: What are the relative influences of soil and hydrology on tree community structure, seedling survival and seedling growth? Do soil and hydrology moderate seedling responses to competition?Location: Nee Soon catchment, Singapore. Methods:We measured and identified trees ≥5 cm diameter in 40 plots measuring 20 m × 20 m each, set up in the wet and dry areas of the catchment, and collected topsoil for analysis of soil texture, pH, and nutrients. We also conducted randomised experiments on seedlings of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Among these, 21 plots occurred within swamp conditions, that is with open water bodies and permanently waterlogged soils with a shallow water table of < 1 m belowground level (hereafter 'swamp plots'). The remaining 19 plots (hereafter 'nonswamp plots') occurred in well-drained areas, with a water table of > 1 m belowground level (Chong et al, 2016(Chong et al, , 2018(Chong et al, , 2021. All trees with a diameter at breast height (DBH) ≥ 5 cm were surveyed in the 20 × 20 m plots.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations
“…Among these, 21 plots occurred within swamp conditions, that is with open water bodies and permanently waterlogged soils with a shallow water table of < 1 m belowground level (hereafter 'swamp plots'). The remaining 19 plots (hereafter 'nonswamp plots') occurred in well-drained areas, with a water table of > 1 m belowground level (Chong et al, 2016(Chong et al, , 2018(Chong et al, , 2021. All trees with a diameter at breast height (DBH) ≥ 5 cm were surveyed in the 20 × 20 m plots.…”
Section: Study Sitementioning
confidence: 99%
“…Seedlings with heights ≥ 20 cm and DBH < 1 cm were surveyed in four randomly placed 1 × 1 m quadrats in each of 37 out of the 40 plots. Plots were surveyed in 2013, 2018, 2019 and 2020. Using the tree data from the 2013 surveys, Chong et al (2021) found that the swamp (i.e. waterlogged) plots had a clearly different tree community from the nonswamp plots, although among species there was a gradient of association where some tree species could be found in both types of conditions.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Leaf litter for decomposition experiments, flammability experiments and litter trait measurements was collected between July 2020 and January 2021 from 10 replicate 400 m 2 long-term vegetation plots (from a total of 40 plots) established in 2013 (described in Chong et al, 2021;Lam et al, 2021Lam et al, , 2022. Freshly fallen leaf litter was collected from 1 m long × 1 m wide litter traps suspended at least 1 m above the ground on a fortnightly basis (Lam et al, 2021).…”
Section: Leaf Materials Collectionmentioning
confidence: 99%